Logic Design as an Enabler to Python Programming Language Teaching - Velaora, Chrysoula; Kakarountas, Athanasios (2019 Panhellenic Conference on Electronics & Telecommunications (PACET), 2019)
In this article the contribution of experiential learning, gamification and emerging technologies to Python programming language teaching is attempted to be sketched. Four scenarios were designed in order to constitute a new teaching proposal for the consolidation of specific modules, incorporating elements of dynamic games, emerging technology and approaching the subject that they are dealing with, in an experiential way in an authentic learning framework by solving problems of everyday life. The main approach of the scenarios is that of social constructivism. A study was conducted to assess the impact of the design of scenarios on learner motivation. The sample of the survey was 15 undergraduate students of the Department of Informatics with Applications in Biomedicine of the University of Thessaly. After completing each scenario, they completed a questionnaire based on the CIS questionnaire survey, which was designed by Keller in 1987 with Likert's 5-step scale questions on the variables motivation, attention-relevance, confidence-satisfaction that are the components of the Kellers ARCS motivation model. The results showed that designing learning scenarios by combining experiential learning, gamification and the use of emerging technologies strengthens the motivation of trainees and leads to the achievement of learning goals.